CURRENT TRENDS IN THE DESIGNS OF LOCOMOTIVES BOGIES - Klimenko, I. V. (Science and Transport Progress, 2003)
The article describes modern designs of the bogies, with approved dynamic parameters, for high speed foreign and Ukrainian-produced diesel and electric locomotives. The current tends in Ukrainian locomotive-building industry have been discussed.